Assessment of Self-Efficacy as a Way to Help Identify Cancer Patients Who Might Benefit from Self-Help Group Attendance?. (7th February 2021) - Christiansen, Nele; Walter, Stefanie; Zomorodbakhsch, Bijan; Sartakhti, Emadaldin Ahmadi; Hübner, Jutta
Abstract: Participating in patient self-help groups is highly recommended to patients in cancer care. Yet, engagement is relatively rare. A total of 253 patients participated in our study conducted as a paper-and-pencil questionnaire. A binominal logistic regression, with interest in participation in self-help groups being the dependent variable, was run. General interest in self-help was high among the respondents. Female gender, higher age, higher education and low self-efficacy were found to significantly predict interest in self-help. Patients reported a lack of information provided by medical professionals. Self-efficacy as a predictor might contribute to characterizing patients who might benefit from self-help group participation.